Hand-Schuller-Christian disease - Sjabaroeddin Loebis; Bistok Saing; Helena Siregar; M. Najib Loebis (Indonesian Pediatric Society, 1981)
A 14-month-old girl was admitted with signs of paleness, weakness and swelling of the lymphnodes in the neck and inguinal. Histopatological examination of the lymphnodes showed histiocytosis X. X-photo of the skull and pelvic bones revealed several osteolysis.Based upon clinical manifestations and histopathological examination this diseases was diagnosed as the rare disease Hand-SchÃ¼ller-Christian disease.